Diversity of Potato Varieties, Farmers Choices and Production Constraints in the Selected Areas of Bangladesh - Hossain, M Z; Kashem, M A; Rashid, M M; Ferdous, F; Molla , M M H (SAARC Journal of Agriculture, 2025)
This study investigated the diversity of potato varieties, farmers’ choices and the underlying reasons for such preference by collecting data from selected areas of Bangladesh. Production constraints of this crop were also identified. The survey was conducted among 553 farmers selected randomly from the 14 most potato-producing districts under four administrative divisions namely Rangpur, Rajshahi, Dhaka and Barishal of the country. A total of 33 potato varieties was reported, of which 24 were high-yielding and 9 were local. The highest number of varieties was reported in the division of Rangpur (29), followed by Rajshahi (16), Dhaka (7) and Barishal (4). Among the reported varieties, the most popular ones were BARI Alu-7 (Diamant), BARI Alu-25 (Asterix), BARI Alu-8 (Cardinal), BARI Alu-29 (Courage) and BARI Alu-13 (Granola). Farmers primarily preferred high-yielding varieties for cultivation, while local varieties were mostly chosen for their taste. About 90% of the farmers faced various constraints during cultivation of potato and the most cited one was “Disease infection” (61.8%) followed by "Insect infestation” (51.2%). Farmers’ responses regarding their choice of variety and production constraints faced by them showed considerable variation among the selected divisions which might be related to local geographical conditions, agricultural practices and socio-economic attributes of the farmers. This study aids policymakers in developing better strategies to boost potato production in Bangladesh. SAARC J. Agric., 23(1): 40-53 (2025)